Distribution pattern of Pb and Zn contamination in rivers near industrial zone in Aceh, Indonesia, revealed by principal component analysis (PCA) - Lelifajri, Lelifajri; Rahmadi, Rahmadi; Idroes, Rinaldi; Supriatno, Supriatno; Safitri, Eka; Nazaruddin, Nazaruddin; Maulana, Ilham; Suhud, Khairi (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2022)
The research aims to evaluate the pollution of Pb and Zn in water, sediment, and Faunus ater samples collected from Krueng Balee (KB) and Kreung Reuleung (KR) Rivers, Aceh, Indonesia. The samples were collected at the upstream, midstream, and downstream of each river and analyzed using Atomic Absorption Spectrophotometry (AAS). The distribution of Pb and Zn pollution was analyzed using Principal Component Analysis (PCA). Our investigation revealed that the presence of Pb and Zn is still safe for water and sediment samples. Nevertheless, Pb and Zn contamination found in F. ater samples had exceeded the national safety limit for food. PCA analysis revealed correlations between samples suggesting the roles of physical and chemical properties of the river in the pollutant retainment. The analysis also indicated the possible antagonism between Pb and Zn accumulation in F. ater which has never been reported previously. We suggest routine monitoring of Pb and Zn concentrations. The role of the surrounding industry in the Pb and Zn pollution should be further studied.